Getting to the Source: Four Perspectives on Leadership - DAY, David Vaughan (Institutional Knowledge at Singapore Management University, 2006)
In the midst of all the innovative business strategies being deployed to respond to globalization, one fundamental aspect often remains unexamined: how leadership is accomplished. What are the most prevalent forms of organizational leadership and their relative strengths and weaknesses, and how can a leader reflect on the type of leadership found in his or her organization and whether that approach is the most appropriate for attaining the organization's strategic goals?